Conservation Agriculture: Gateway for Sustainable Intensification of Smallholder Systems - Jat, Mangi Lal; Sidhu, Harminder S.; Kalvaniya, Kailash C.; Rana, Dharamvir Singh (2021)
The Conservation Agriculture (CA) practices with increased acceptance across the globe are being considered as harbinger for sustainable intensification of smallholder production systems. Its positive impact on natural resources, and adaptation to and mitigation of climate change effects are widely acknowledged. In developing world specially Asia and Africa, CA is a relatively new introduction and hence capacity development is vital for development, adaptation and scaling CA based technologies for impact at scale on smallholder farmers in these regions. The training objectives were centered on understanding Conservation Agriculture (CA) and its applications in Asia and Africa. The key findings from the training were that participants need more collaboration with educational institutions and stakeholders when it comes to new knowledge and information, that they would need to re-visit the research, education, and extension linkages vis-à-vis the CA practices, and that the information gained during the course had to cascade to students and the farming community. The participants were pleased that the CA practices was out and that they could begin to explore different areas they could implement on-site in their contexts. Furthermore, participants noted that the CA practices was a useful technology to their work situations. Finally, the participants stated that the partnerships they had with the different experts represented by the different institutions was paramount to the subsequent programs and activities, that would follow the CA practices.